Incidence of using substances among high school students and affecting factorsa - Akkuş, Dilek; Karaca, Aysel; Konuk Şener, Dilek; Ankaralı, Handan (Journal of Dependence, 2016)
Objective: Substance use is an important subject that has been addressed frequently among adolescents in recent years. The aim of this study is to determine the incidence of substance use among high school students and the factors affecting the use of these substances. Method: This sectional-type study was carried out with 1997 students who were studying in three high schools between 2015-2016 academic year. All of the volunteer students were enrolled in the study that was designed by cluster sampling method. Data were collected by a questionnaire which was developed by the researchers. Questionnaires were distributed to the students by peer educators within the class, and the forms were filled under the supervision of the researchers. Data were analyzed by using mean, standard deviation, number and frequencies, chi-square and multiple polytomous logistic regression model. Results: In this study ratio of students who have used marijuana once in their lives is 3,6%, who have used ecstasy is 1,6%, and ratio for the volatile is 3,5%. For all of the substances, it is determined that frequency of drug usage is more in students who is male, studied in industrial vocational schools and 12nd grade than others. In addition to this, it is determined that the factors of friends who use substances, unsuccessful school grades, absenteeism, disciplinary punishments and trouble with police increase the usage of substances. Conclusion: Students’ illegal drug usage frequency shows similarity with study results which have done in other countries and Turkey. It is seen that student sociodemographic characteristics, family, friend and school features are important factors which affect the frequency of drug usage.